Correction to: Experimental determination of the temperature dependence of oxygen-isotope fractionation between water and chitinous head capsules of chironomid larvae - Alex Lombino; Tim Atkinson; Stephen J. Brooks; Darren R. Gröcke; Jonathan Holmes; Vivienne J. Jones; Jim D. Marshall (Journal of Paleolimnology, 2021)

Experimental determination of the temperature dependence of oxygen-isotope fractionation between water and chitinous head capsules of chironomid larvae - Alex Lombino; Tim Atkinson; Stephen J. Brooks; Darren R. Gröcke; Jonathan Holmes; Vivienne J. Jones; Jim D. Marshall (Journal of Paleolimnology, 2021)
Oxygen-isotope values of invertebrate cuticle preserved in lake sediments have been used in palaeoenvironmental reconstructions, generally with the assumption that fractionation of oxygen isotopes between cuticle and water ( $$\upalpha_{\text{cuticle}-\text{H}_{2}\text{O}}$$ α cuticle - H 2 O ) is independent of temperature. We cultured chironomid larvae in the laboratory with labelled oxygen-isotope water and across a range of closely controlled temperatures from 5 to 25 °C in order to test the hypothesis that fractionation of oxygen isotopes between chironomid head capsules and water ( $$\upalpha_{\text{chironomid}-\text{H}_{2}\text{O}}$$ α chironomid - H 2 O ) is independent of temperature. Results indicate that the hypothesis can be rejected, and that $$\upalpha_{\text{chironomid}-\text{H}_{2}\text{O}}$$ α chironomid - H 2 O decreases with increasing temperature. The scatter in the data suggests that further experiments are needed to verify the relationship. However, these results indicate that temperature-dependence of $$\upalpha_{\text{chironomid}-\text{H}_{2}\text{O}}$$ α chironomid - H 2 O should be considered when chironomid δ 18 O is used as a paleoenvironmental proxy, especially in cases where data from chironomids are combined with oxygen-isotope values from other materials for which fractionation is temperature dependent, such as calcite, in order to derive reconstructions of past water temperature.

Trawl fishing impacts on the status of seabed fauna in diverse regions of the globe - Tessa Mazor; C. Roland Pitcher; Wayne Rochester; Michel J. Kaiser; Jan G. Hiddink; Simon Jennings; Ricardo Amoroso; Robert A. McConnaughey; Adriaan D. Rijnsdorp; Ana M. Parma; Petri Suuronen; Jeremy Collie; et al. (Fish and Fisheries, 2021)
Bottom trawl fishing is a controversial activity. It yields about a quarter of the world's wild seafood, but also has impacts on the marine environment. Recent advances have quantified and improved understanding of large‐scale impacts of trawling on the seabed. However, such information needs to be coupled with distributions of benthic invertebrates (benthos) to assess whether these populations are being sustained under current trawling regimes. This study collated data from 13 diverse regions of the globe spanning four continents. Within each region, we combined trawl intensity distributions and predicted abundance distributions of benthos groups with impact and recovery parameters for taxonomic classes in a risk assessment model to estimate benthos status. The exposure of 220 predicted benthos‐group distributions to trawling intensity (as swept area ratio) ranged between 0% and 210% (mean = 37%) of abundance. However, benthos status, an indicator of the depleted abundance under chronic trawling pressure as a proportion of untrawled state, ranged between 0.86 and 1 (mean = 0.99), with 78% of benthos groups > 0.95. Mean benthos status was lowest in regions of Europe and Africa, and for taxonomic classes Bivalvia and Gastropoda. Our results demonstrate that while spatial overlap studies can help infer general patterns of potential risk, actual risks cannot be evaluated without using an assessment model that incorporates trawl impact and recovery metrics. These quantitative outputs are essential for sustainability assessments, and together with reference points and thresholds, can help managers ensure use of the marine environment is sustainable under the ecosystem approach to management.

Behavioral repertoire assessment of Bengal tigers (Panthera tigris) with focus on thermoregulatory behavior - Judith A. Stryker; Jim L. Atkinson; Robert D. Brown; David Barney; J. Andy B. Robinson; Jay Duncan; Esther J. Finegan (International Journal of Biometeorology, 2019)

Exercise as a synchroniser of human circadian rhythms: an update and discussion of the methodological problems - Greg Atkinson; Ben Edwards; Thomas Reilly; Jim Waterhouse (European Journal of Applied Physiology, 2007)

Evaluating perturbations and developing restoration strategies for inland wetlands in the Great Lakes basin - Naomi E. Detenbeck; Susan M. Galatowitsch; Jim Atkinson; Helen Ball (Wetlands, 1999)